The Moderating Role of Profit and Loss Sharing in the Relationship Between Marketability and Profitability in Islamic Commercial Banks in Indonesia - Catur Surya Perwira; Sugeng Wahyudi (Jurnal Manajemen Bisnis, 2022)
The problem phenomenon in this study is the low growth of marketability, profitability, profit and loss sharing of Islamic banks in 2014-2019. This study aims to analyze the factors that influence the profitability of Islamic commercial banks in Indonesia for the period 2014-2019. This research method uses quantitative with secondary data sources. The results of the study of factors that have a significant positive effect are Profit and loss sharing on profitability with a t-count value of 6.13091 > t-table 1.645. Marketability to profitability with t-count of 2.00583 > t-table 1.645 and which has a significant negative effect. Marketability on profit and loss sharing t-count 6.80506 > t-table 1.645 and original sample coefficient 1 -0.35806.